Digital Dialogue: Leveraging Microsoft Word for Effective Peer Feedback - Puspita, Nurul (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2024)
Peer feedback is a significant instructional technique in the learning process, providing students with varied perceptions and insights to expand their work. In the digital age, Microsoft Word provides numerous features that can increase the effectiveness of peer feedback. Therefore, the purpose of this research is to explore how students can utilize Microsoft Word for providing and receiving constructive peer feedback. This research would focus on understanding and interpreting the meaning of interpretation, which is qualitative research. Observations and document analysis would be used to gather comprehensive data on the use of Microsoft Word. In addition, the results of the data would be analyzed iteratively. In conclusion, Microsoft Word offers a wide range of capabilities that help improve students' peer review processes. The impact of the research lies on the use of tools like